2018
DOI: 10.1111/jcpe.12872
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional association between oral health and retinal microcirculation

Abstract: Our results point towards an association between periodontal conditions and AVR in men. Periodontitis may impact microvascular endothelium function. Improving oral health to reduce periodontitis might lead to reduced risk for other age-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Among participants with functional atherosclerosis, low CIMT values indicate a deficiency of the capacity to maintain the microcirculation and high CIMT values indicate more disruption of the microcirculation. Since the status of the microcirculation might be associated with oral health [ 30 ], CIMT can be associated with tooth loss only among participants without functional atherosclerosis [ Table 3 and Figure 1 b,c]. In the present study, a small but significant positive association between CIMT and CAVI was observed among participants without functional atherosclerosis [ Table 4 and Figure 1 a], but not among participants with functional atherosclerosis [ Table 4 and Figure 1 d].…”
Section: Discussionmentioning
confidence: 44%
“…Among participants with functional atherosclerosis, low CIMT values indicate a deficiency of the capacity to maintain the microcirculation and high CIMT values indicate more disruption of the microcirculation. Since the status of the microcirculation might be associated with oral health [ 30 ], CIMT can be associated with tooth loss only among participants without functional atherosclerosis [ Table 3 and Figure 1 b,c]. In the present study, a small but significant positive association between CIMT and CAVI was observed among participants without functional atherosclerosis [ Table 4 and Figure 1 a], but not among participants with functional atherosclerosis [ Table 4 and Figure 1 d].…”
Section: Discussionmentioning
confidence: 44%
“…Despite the universality of Canada's medical care system, and considerable amount of evidence on the association between oral and systemic health , publicly funded dental care remains limited and only targets specific populations in Canada. Dental care has an important role to play in the early diagnosis of oral and systemic diseases, in improving oral health and certain systemic health conditions, and in the overall quality of life . Therefore, it is arguably necessary to provide equitable access to dental care for the entire population.…”
Section: Introductionmentioning
confidence: 99%
“…These results imply a possible link between periodontitis and ocular vascular disease. Indeed, a cross-sectional study showed that severe periodontitis was inversely correlated with the arteriovenous ratio, suggesting that periodontitis affects microvascular endothelium function in the retina [ 23 ]. A cohort study also demonstrated that patients with periodontitis have a higher risk of developing age-related macular degeneration than those without periodontitis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%